2012
DOI: 10.3390/w4010237
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Sea Level Rise and Coastal Storm Surge from Southern and Eastern Africa: A Case Study Near Durban, South Africa

Abstract: Recent coastal storms in southern Africa have highlighted the need for more proactive management of the coastline. Within the southern and eastern African region the availability of coastal information is poor. The greatest gap in information is the likely effects of a combination of severe sea storms and future sea level rise (SLR) on the shoreline. This lack of information creates a barrier to informed decision making. This research outlines a practical localized approach to this problem, which can be applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 29 publications
(31 reference statements)
1
38
0
Order By: Relevance
“…The CP06 resembles a pattern similar to TC's south of Madagascar. TC's located within this region have been cited to drive large swells toward the KZN Coast (Mather and Stretch, 2012). The CP05 resembles low-pressure systems over the interior.…”
Section: Dominant Cp Classesmentioning
confidence: 99%
See 2 more Smart Citations
“…The CP06 resembles a pattern similar to TC's south of Madagascar. TC's located within this region have been cited to drive large swells toward the KZN Coast (Mather and Stretch, 2012). The CP05 resembles low-pressure systems over the interior.…”
Section: Dominant Cp Classesmentioning
confidence: 99%
“…A number of weather types have been cited as the drivers of this wave climate. For example tropical cyclones, mid-latitude (extra-tropical) cyclones and cut off lows (Rossouw et al, 1982;Corbella and Stretch, 2012c;Mather and Stretch, 2012). The location and persistence of tropical cyclones (TC's) are believed to drive large wave events that cause severe beach erosion in KZN (Corbella and Stretch, 2012c;Mather and Stretch, 2012).…”
Section: Case Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea has been explored in many countries (e.g. Breetzke et al, 2008;Hart, 2011;Mather and Stretch, 2012;Ryan et al, 2012;Barron et al, 2012;Roca and Villares, 2012). National governments have advocated its adoption: the UK is hoping for major coastal realignment in England and Wales by 2030 (Defra and EA, 2002;CCC, 2013;O"Riordan et al, 2014); MR in the USA aims at assisting coastal risk reduction requirements for unprotectable areas (NWF, 1998;NOAA, 2014;Kousky, 2014, Siders, 2013.…”
Section: Opposition Advocacy and Limitationsmentioning
confidence: 99%
“…Two papers in this special issue by Dangendorf et al [21] and Mather et al [22] explore some of the uncertainties associated with changes in the coastal flood management system associated with sea level rise; even more importantly, development and land management choices which can increase vulnerability and exposure to flooding. For example, analysis by Huong and Pathirana [23] in Vietnam showed that flood depths in Can Tho could increase by 20% from urbanization alone.…”
Section: Predicting and Modeling Floods: Taking Into Account Human Acmentioning
confidence: 99%